Stereological analysis of liver biopsy histology sections as a reference standard for validating non-invasive liver fat fraction measurements by MRI - St Pierre, T.; House, M.; Bangma, S.; Pang, W.; Bathgate, A.; Gan, E.; Ayonrinde, Oyekoya; Bhathal, P.; Clouston, A.; Olynyk, John; Adams, L. (Public Library of Science, 2016)
© 2016 St. Pierre et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.Background and Aims: Validation of non-invasive methods of liver fat quantification requires a reference standard. However, using standard histopathology assessment of liver biopsies is problematical because of poor repeatability. We aimed to assess a stereological method of measuring volumetric liver fat fraction (VLFF) in liver biopsies and to use the method to validate a magnetic resonance imaging method for measurement of VLFF. Methods: VLFFs were measured in 59 subjects (1) by three independent analysts using a stereological point counting technique combined with the Delesse principle on liver biopsy histological sections and (2) by three independent analysts using the HepaFat-Scan® technique on magnetic resonance images of the liver. Bland Altman statistics and intraclass correlation (IC) were used to assess the repeatability of each method and the bias between the methods of liver fat fraction measurement. Results: Inter-analyst repeatability coefficients for the stereology and HepaFat-Scan® methods were 8.2 (95% CI 7.7-8.8)% and 2.4 (95% CI 2.2-2.5)% VLFF respectively. IC coefficients were 0.86 (95% CI 0.69-0.93) and 0.990 (95% CI 0.985-0.994) respectively. Small biases (=3.4%) were observable between two pairs of analysts using stereology while no significant biases were observable between any of the three pairs of analysts using Hepa-Fat-Scan®. A bias of 1.4±0.5% VLFF was observed between the HepaFat-Scan® method and the stereological method. Conclusions: Repeatability of the stereological method is superior to the previously reported performance of assessment of hepatic steatosis by histopathologists and is a suitable reference standard for validating non-invasive methods of measurement of VLFF.